Mechanics of cutaneous wound rupture. Issue 15 (7th November 2016) - Swain, Digendranath; Gupta, Anurag
Abstract: A cutaneous wound may rupture during healing as a result of stretching in the skin and incompatibility at the wound–skin interface, among other factors. By treating both wound and skin as hyperelastic membranes, and using a biomechanical framework of interfacial growth, we study rupturing as a problem of cavitation in nonlinear elastic materials. We obtain analytical solutions for deformation and residual stress field in the skin–wound configuration while emphasizing the coupling between wound rupture and wrinkling in the skin. The solutions are analyzed in detail for variations in stretching environment, healing condition, and membrane stiffness.